2022
DOI: 10.3390/uro2010006
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Extracts (Glycine Max) with Curcuma, Boswellia, Pinus and Urtica Are Able to Improve Quality of Life in Patients Affected by CP/CPPS: Is the Pro-Inflammatory Cytokine IL-8 Level Decreasing the Physiopathological Link?

Abstract: The present study evaluates the efficacy of a combination of soyabean extracts associated with Curcuma Longa, Boswellia, Pinus pinaster and Urtica dioica (PROSTAFLOG®) in patients affected by CP/CPPS, through the evaluation of interleukin-8 (IL-8) plasma seminal levels. All patients diagnosed with CP/CPPS, attending the same urologic center, were enrolled in this randomized, controlled phase III study. Participants were randomized to receive oral capsules of PROSTAFLOG® (two capsules at bedtime every 24 h) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Several authors reported that numerous reactive oxygen classes have been involved in seminal plasma parameters decline [21,22]. In particular, some metabolites in peroxidative damage are associated with oligospermia and teratospermia [23], such as prostate tissue damage [24,25]. In this sense, the use of anti-oxidant drugs is an important pillar in the management of hypofertile males.…”
Section: Results In the Context Of Previous Studiesmentioning
confidence: 99%
“…Several authors reported that numerous reactive oxygen classes have been involved in seminal plasma parameters decline [21,22]. In particular, some metabolites in peroxidative damage are associated with oligospermia and teratospermia [23], such as prostate tissue damage [24,25]. In this sense, the use of anti-oxidant drugs is an important pillar in the management of hypofertile males.…”
Section: Results In the Context Of Previous Studiesmentioning
confidence: 99%
“…General characteristics of the study participants were expressed with descriptive statistics (means, standard deviations or ranges). The calculation of the sample size needed for enrollment was based on the expected questionnaire results (improvement of quality of life) in line with published results from other studies ( 14 , 20 , 21 ). The required sample size was calculated under the following conditions: Difference between the groups, 35% of patients who reach a reduction in 15% of the NIH-CPSI total score; α error level, 0.05 two-sided; statistical power, 80%; and anticipated effect size, Cohen's d=0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several other Extracorporeal shock wave therapy in association with bromelain and escin for the management of patients affected by chronic prostatitis/chronic pelvic pain syndrome approaches have been used and evaluated for the management of patients with CP/CPPS, such as thermobalancing, transurethral needle ablation, transcutaneous electrical nerve stimulation or sono-electromagnetic therapy, and patients treated using these approaches have exhibited a significant clinical improvement (5)(6)(7). On the other hand, phytotherapy has been used over the past years with satisfactory results as regards the relief of symptoms and quality of life (7,13,14). Several studies have been published on the roles of quercetin, bee pollen, pumpkin seed oil, eviprostat or terpene mixture, with promising results (7,13,14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations